Dam Renovation to Prolong Reservoir Life and Mitigate Dam Impacts - Kondolf, Mathias; Yi, Jaeeung (Water (Switzerland), 2022)
Dams are essential to society, yet have tremendous environmental impacts, for which there is an increasing interest in mitigation. At the same time, sedimentation threatens the sustainability of reservoir storage and reservoir functions. We use the term dam renovation to encompass a wide range of measures, including dam rehabilitation, a term commonly used for structural retrofits, typically of the dam structure or spillway, fishway retrofits for migratory fish passage, reservoir reoperation, which involves modifying dam operations to improve flow regimes for ecological purposes, and sustainable sediment management, which includes measures to pass sediment through or around dams, as well as other mechanical measures to restore sediment connectivity. Compared to dam renovation, an inordinate amount of literature has been published on the topic of dam removal. While in some cases dam removal is a practical way to improve river condition and to resolve the safety problems of aging dams, the reality is that most dams in existence today will remain for the foreseeable future, provided they do not fill with sediment, or their structures deteriorate to the point of failure. Thus, it is imperative that we understand the options available to renovate dams with poor environmental performance or whose sustainability is threatened.
Keywords: Dam impacts; Dam rehabilitation; Dam removal; Dam renovation; Reservoir storage; River restoration; Sediment flushing; Sediment management; Sediment sluicing; Sustainable sediment management; dam rehabilitation; dam removal; dam renovation; fishways; river restoration; sediment flushing; sediment sluicing; sustainable sediment management